EATING DISORDERS (ANOREXİA, BULİMİA, AND BİNGE EATİNG) - Musai, Musa; Şabani, Yasemın (International Scientific Journal Vision, 2024)
Eating disorders encompass a range of psychological conditions that contribute to the development of unhealthy eating habits. Individuals with eating disorders, due to dissatisfaction with their body shape and weight and the distress caused by this situation, exhibit many unhealthy attitudes and behaviors. The occurrence of eating disorders is not attributed to a single factor. These diseases are generally associated with genetic and biological predispositions. It is assumed that they emerge through the interaction of environmental, sociocultural, and spiritual factors. In the DSM-5 classification, the three best characterized typical eating disorders are anorexia nervosa, bulimia nervosa, and binge eating disorder.